(untitled) (Conferencea, 2024)
The concept of time embodies the reflection of the era and activity, the interpretation of the established culture, the rhythm of social time and the effectiveness of prognostic consciousness. All these moments define the historical “paradigm” of time. This article considers a comparative approach, in which the national-cultural specificity of one language is determined in relation to another language, and an introspective approach, in which the national specificity of a language is viewed through the eyes of its speakers.